ARTIFICIAL INTELLIGENCE AND ITS ROLE IN MODERN EDUCATIONAL MANAGEMENT AND PLANNING (UNIZIK Journal of Educational Management and Policy, 2025)
The integration of Artificial Intelligence (AI) into educational management and planning has fundamentally altered how institutions optimize operations, formulate policies, and enhance learning experiences. This study critically examines AI’s transformative potential, practical applications, and ethical implications in educational settings. By synthesizing recent research, the paper explores how AIdriven tools—such as predictive analytics, automation, and intelligent decision-support frameworks—are streamlining administrative workflows, improving resource allocation, and enabling evidence-based strategies. Additionally, the study addresses key challenges, including infrastructure limitations, ethical concerns, and resistance to change, while proposing actionable recommendations for responsible AI adoption. The findings underscore AI’s capacity to revolutionize educational systems while emphasizing the need for thoughtful implementation and oversight.
Keywords: Artificial Intelligence, Educational Planning, Educational Management, Intelligent Decision Support Systems, Predictive Analytics